'New Aging': Designing Architecture for All Ages. (March 2014) - Hollwich, Matthias; Hoffman, Matthew; Farrelly, Lorraine
Abstract The US is on the brink of demographic transformation, with the bulging generation of baby boomers about to reach retirement. In 2008, New York‐based architects Hollwich Kushner (HWKN) anticipated this shift by instigating a 'New Aging' initiative that set out to explore imaginative solutions in architecture and urbanism to age‐related challenges. Here Matthias Hollwich with Matthew Hoffman of HWKN explain why attitudes and approaches to ageing have to change; and why old age needs to be 'acknowledged as a state of human existence' that fully 'deserves preparation, anticipation and excitement'.